2004
DOI: 10.1038/nsmb800
|View full text |Cite
|
Sign up to set email alerts
|

PH domain of ELMO functions in trans to regulate Rac activation via Dock180

Abstract: The members of the Dock180 superfamily of proteins are novel guanine nucleotide exchange factors (GEF) for Rho family GTPases and are linked to multiple biological processes from worms to mammals. ELMO is a critical regulator of Dock180, and the Dock180-ELMO complex functions as a bipartite GEF for Rac. We identified a mechanism wherein the PH domain of ELMO, by binding the Dock180-Rac complex in trans, stabilizes Rac in the nucleotide-free transition state. Mutagenesis studies reveal that this ELMO PH domain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 31 publications
4
120
1
Order By: Relevance
“…In the first pathway, the proteins CED-2, CED-5 and CED-12 (mammalian homologues CrkII, Dock180 and ELMO, respectively) function to activate CED-10 (Rac) and worms deficient in any of these protein can be rescued by overexpression of Ced-10. 49 In the second group, the candidate receptor CED-1 (CD91/LRP) probably recognises an unknown ligand on the apoptotic cell and signals via its cytoplasmic tail to the adaptor protein CED-6 (hCED-6/ GULP), whereas CED-7 (ABCA?) is thought to play a role in membrane dynamics.…”
Section: Engulfmentmentioning
confidence: 99%
“…In the first pathway, the proteins CED-2, CED-5 and CED-12 (mammalian homologues CrkII, Dock180 and ELMO, respectively) function to activate CED-10 (Rac) and worms deficient in any of these protein can be rescued by overexpression of Ced-10. 49 In the second group, the candidate receptor CED-1 (CD91/LRP) probably recognises an unknown ligand on the apoptotic cell and signals via its cytoplasmic tail to the adaptor protein CED-6 (hCED-6/ GULP), whereas CED-7 (ABCA?) is thought to play a role in membrane dynamics.…”
Section: Engulfmentmentioning
confidence: 99%
“…To provide insight into the molecular context in which Dictyostelium Dock180-related proteins function, we isolated the DockD complex and uncovered DdELMO1, a Dictyostelium ELMO protein. Among the five ELMO domain-containing proteins that are encoded by the Dictyostelium genome, DdELMO1 is the only one that contains the proline-rich region at the C-terminus that mediates Dock180-ELMO interaction (Supplemental Figure S2; Lu et al, 2004). According to the steric-inhibition model proposed by Lu et al, at the basal state, the N-terminal SH3 domain of Dock180 binds to the distant CZH2 domain and negatively regulates the function of the protein as it prevents the interaction with Rac.…”
Section: Dockd Forms a Complex With Dictyostelium Elmo1 And Rac Gtpasesmentioning
confidence: 99%
“…The amino-terminal 558 amino-acid residues (N-term) were necessary for targeting of the ELMO-Dock180 complex to the membrane 14,17 , whereas the carboxy-terminal 196 residues (C-term) were necessary for binding Dock180 and for optimal Rac activation 15,16 . Because the receptor(s) upstream of ELMO1 during engulfment were not known, we performed a yeast two-hybrid screen, with N-term as bait.…”
mentioning
confidence: 99%
“…Previous studies revealed two 'functional' regions within ELMO1 and its Caenorhabditis elegans homologue CED-12 during phagocytosis 5,[14][15][16][17] . The amino-terminal 558 amino-acid residues (N-term) were necessary for targeting of the ELMO-Dock180 complex to the membrane 14,17 , whereas the carboxy-terminal 196 residues (C-term) were necessary for binding Dock180 and for optimal Rac activation 15,16 .…”
mentioning
confidence: 99%